Solve for n -67=-(4-6n)+3n

Math
-67=-(4-6n)+3n
Rewrite the equation as -(4-6n)+3n=-67.
-(4-6n)+3n=-67
Simplify -(4-6n)+3n.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-1⋅4-(-6n)+3n=-67
Multiply -1 by 4.
-4-(-6n)+3n=-67
Multiply -6 by -1.
-4+6n+3n=-67
-4+6n+3n=-67
Add 6n and 3n.
-4+9n=-67
-4+9n=-67
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Add 4 to both sides of the equation.
9n=-67+4
Add -67 and 4.
9n=-63
9n=-63
Divide each term by 9 and simplify.
Tap for more steps…
Divide each term in 9n=-63 by 9.
9n9=-639
Cancel the common factor of 9.
Tap for more steps…
Cancel the common factor.
9n9=-639
Divide n by 1.
n=-639
n=-639
Divide -63 by 9.
n=-7
n=-7
Solve for n -67=-(4-6n)+3n

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top